Modified vaccinia virus Ankara expressing the hemagglutinin of pandemic (H1N1) 2009 virus induces cross‐protective immunity against Eurasian 'avian‐like' H1N1 swine viruses in mice. Issue 3 (23rd December 2013) - Castrucci, Maria R.; Facchini, Marzia; Di Mario, Giuseppina; Garulli, Bruno; Sciaraffia, Ester; Meola, Monica; Fabiani, Concetta; De, Maria A.; Cordioli, Paolo; Siccardi, Antonio; Kawaoka, Yoshihiro; Donatelli, Isabella
<x xml:space="preserve">Abstract</x> Objectives To examine cross‐reactivity between hemagglutinin (HA) derived from A/California/7/09 (CA/09) virus and that derived from representative Eurasian "avian‐like" (EA) H1N1 swine viruses isolated in Italy between 1999 and 2008 during virological surveillance in pigs. Design Modified vaccinia virus Ankara (MVA) expressing the HA gene of CA/09 virus (MVA‐HA‐CA/09) was used as a vaccine to investigate cross‐protective immunity against H1N1 swine viruses in mice. Sample Two classical swine H1N1 (CS) viruses and four representative EA‐like H1N1 swine viruses previously isolated during outbreaks of respiratory disease in pigs on farms in Northern Italy were used in this study. Setting Female C57BL/6 mice were vaccinated with MVA/HA/CA/09 and then challenged intranasally with H1N1 swine viruses. Main outcome measures Cross‐reactive antibody responses were determined by hemagglutination‐ inhibition (HI) and virus microneutralizing (MN) assays of sera from MVA‐vaccinated mice. The extent of protective immunity against infection with H1N1 swine viruses was determined by measuring lung viral load on days 2 and 4 post‐challenge. Results and Conclusions Systemic immunization of mice with CA/09‐derived HA, vectored by MVA, elicited cross‐protective immunity against recent EA‐like swine viruses. This immune protection was related to the levels of cross‐reactive HI antibodies in the sera of the immunized mice and was dependent on the similarity of the antigenic site Sa of H1 HAs. Our findings suggest that the herd immunity elicited in humans by the pandemic (H1N1) 2009 virus could limit the transmission of recent EA‐like swine HA genes into the influenza A virus gene pool in humans.